Corporate governance theories from unconventional perspective - Htay, Sheila Nu Nu; Salman, Syed Ahmed; Mydin Meera, Ahamed Kameel (2013)
Corporate governance theories, namely the agency theory, stewardship theory and stakeholder theory, have been used in developing the best practices of corporate governance. However, corporate scandals leading to the downfall of financial giants such as Enron and WorldCom in 2003 and the global financial crisis of 2008-2009 have revealed serious inadequacies in the effectiveness of corporate governance. Therefore, these governance failures motivate the researchers to revisit and evaluate corporate governance theories from the ethical point of view. The main aim of this study is to propose “The Universal Corporate Governance Theory” which is developed based on the ethical teachings of Christians, Judaism, Islam, Sikh, Hinduism and Buddhism. It is expected that this ethical based theory will be applicable and acceptable for all types of organizations at any space and time. It is also believed that if the top corporate players are molded by this proposed theory, it will bring the social and economic justice what we are dreaming to achieve.